Visual Outcome and Causes of Decreased Vision in Traumatic Pediatric Cataracts (Medical Forum Monthly, 2022)
Objective: Pediatric Ocular trauma is a leading cause of vision loss and is avoidable. Hence, blindness can be prevented by awareness regarding causes and consequences of eye trauma in children by health education. Therefore, this study was intended to assess the visual outcome associated with cataract surgery in traumatic pediatric cataract.Study Design: Quasi experimental studyPlace and Duration of Study: This study was conducted at the Ophthalmology Department, Al Ibrahim Eye Hospital, Karachi from September 2021 till March 2022.Materials and Methods: A total of 68 children aged 5 to 15 years with presenting history of trauma either open globe or closed globe with no associated retinal pathology and children with 3 months follow up were included in this study. Data analysis was done using SPSS V 23.0. Categorical variables like gender, mode and duration of trauma, surgical procedure, pre and post-operative visual acuity were documented as frequencies and percentages.Results: The results showed that out of 68 children, 46(67.6%) were boys and 22(32.4%) were girls. With regard to mode of injury, blunt trauma was observed in 30(44.1%) children and penetrating trauma was observed in 38(55.9%) children. The most common causative agents were wooden stick 26(38.2%), followed by stones 10(4.7%). Postoperative complication revealed that 16(23.5%) children developed corneal opacity, amblyopia developed in 18(26.5%) children Postoperative uveitis developed in 20(29.4%) children whereas decentered IOL was reported in 18(26.5%) children.Conclusion: This study concluded that boys were more expected to affect from traumatic cataract as compared to girls. The leading object causing injury was wooden stick. Most of the eyes had effective intra-ocular lens implantation in cataract surgical treatment while best corrected visual acuity enhanced in a moderate percentage of these patients. However, visual impairment was observed in few eyes owing to amblyopia and Uveitis.